2014
DOI: 10.1186/s12968-014-0081-1
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular systolic function and the pattern of late-gadolinium-enhancement independently and additively predict adverse cardiac events in muscular dystrophy patients

Abstract: BackgroundCardiac involvement is a frequent finding in patients with Duchenne (DMD) and Becker (BMD) muscular dystrophies. With this study, we aimed at elucidating the relationship between the phenotypic expression of cardiac involvement and the occurrence of adverse cardiac events in DMD/BMD patients.MethodsEighty-eight male DMD/BMD patients (age 29 ± 14 yrs) were prospectively enrolled. All patients underwent cardiovascular magnetic resonance (CMR) comprising cine- and late-gadolinium-enhancement (LGE)-CMR a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
63
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(64 citation statements)
references
References 32 publications
1
63
0
Order By: Relevance
“…Further evidence has emerged showing that particularly an impaired LVEF and a "transmural" pattern of LGE appear to predict the occurrence of adverse cardiac events in DMD patients. 20 The question remains how to clinically interpret findings of low grade LGE when this is mostly associated with normal cardiac function, or the rare case with extensive LGE but relatively preserved LVEF? LGE is based on the delayed washin and wash-out of gadolinium in myocardial areas with increased extracellular space due to fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Further evidence has emerged showing that particularly an impaired LVEF and a "transmural" pattern of LGE appear to predict the occurrence of adverse cardiac events in DMD patients. 20 The question remains how to clinically interpret findings of low grade LGE when this is mostly associated with normal cardiac function, or the rare case with extensive LGE but relatively preserved LVEF? LGE is based on the delayed washin and wash-out of gadolinium in myocardial areas with increased extracellular space due to fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, clinical implications of LGE in DMD were demonstrated when Florian et al [24] showed that “transmural” LGE was associated with more adverse events in muscular dystrophy subjects and Tandon et al [25] found correlations between the presence of LGE, LVEF and genotype. Soslow et al also looked at post-contrast T1 ratios and found lower ratios in DMD subjects compared to controls, even in LGE negative subjects [26].…”
Section: Discussionmentioning
confidence: 99%
“…148,[158][159][160] Myocardial fibrosis burden, quantified as number of LGE-positive myocardial segments, is associated with decline in EF, 161 and transmural LGE was also recently reported to have additive value above LVEF alone in predicting hospitalization for HF or occurrence of ventricular tachycardia. 162 Abnormalities in segmental circumferential strain, detectable by echocardiography and CMR, may also be an early biomarker of myocardial dysfunction in DMD, preceding the development of myocardial fibrosis. 147,163 There is also emerging evidence that female DMD, and to a lesser extent BMD, carriers have subclinical cardiac involvement, characterized by reduced LVEF or subepicardial LV lateral free wall LGE on CMR.…”
Section: Cardiac Evaluation In Dmd and Bmdmentioning
confidence: 99%